Penerapan Strategi Active Learning untuk Meningkatkan Hasil Belajar Bahasa Inggris Siswa Kelas X IPS.1 SMA Negeri 14 Pekanbaru - Kesuma Hastuti (Journal on Education, 2022)
This research was conducted from February to March 2022. This research aims to improve the English learning outcomes of class X IPS.1 SMA Negeri 14 Pekanbaru by implementing an active learning strategy. The subjects of this study were IPS.1 class, which consisted of 35 people, consisting of 12 boys and 23 girls. The research instruments included syllabus, lesson plans, observation sheets of teacher and student activities, student worksheets, and daily test questions. The implementation of this classroom action research took place in two cycles. Each cycle is carried out for two meetings and one daily repetition. The implementation of the two cycles in this study was to see the changes that occurred in each meeting using the active learning strategy presented during the lesson. Sources of data from this study were all students who were research subjects and teachers who were involved in this research. Data analysis in this study used descriptive analysis. The results showed that teacher activity, student completeness, and student learning outcomes increased by an average of 65.71% in cycle I and increased in cycle II by 91.43%. Student activity based on research results increased from 57.96% in cycle I to 87.65% in cycle II. Teacher activity increased from 60% in cycle I to 90% in cycle II. Based on the results of the study it can be concluded that the application of an active learning strategy can improve student learning outcomes in class X IPS.1 SMA Negeri 14 Pekanbaru.